O vrstah in pomenih gibnih pozdravov - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 2014)
Salutations are various conventional messages upon someone's arrival or departure, or when meeting someone, expressing confirmation of the existing social and interpersonal relations, respect, honour, affection, warmth, welcomeness, good intentions, various beliefs and affiliation. Verbal salutations are meant to be heard, salutation gestures to be seen. Salutation gestures are body gestures, postures, or other visible salutation acts consisting of various elements. There are much less salutation gestures than verbal salutations, but they are probably much older, because similar gestures and signalling acts, similar in meaning, have been found with primates and some other mammals. The opposite of salutation gestures are threatening, shaming, contemptuous, and demeaning gestures. Salutation gestures can be divided based on their physical modes and sensory perception. Salutations without touching include various gestures with raised open hands, joined palms held at chest level, baring one's head, standing up, bowing, genuflection, and prostration. Touching salutations include various forms of shaking hands, embraces, touching noses, kisses. Salutation gestures are often synchronous or sequences of various elements, most often accompanied by verbal salutations. Various gestures and acts (most often gifting), which usually are not salutations, may become salutations in some cultural systems or in special circumstances.
Keywords: ethnology; etnologija; komunikacija; pozdravljanje; pozdravi; Slovenia; Slovenija; zgodovinski pregledi